Plasma gelsolin as a biomarker of acute rheumatic carditis. (18th November 2014) - Argun, Mustafa; Baykan, Ali; Narin, Figen; Özyurt, Abdullah; Pamukçu, Özge; Elmalı, Ferhan; Üzüm, Kazım; Narin, Nazmi
Abstract Background Acute rheumatic fever is an autoimmune, inflammatory, and multi-systemic disease secondary to pharyngitis and is caused by group A streptococcus. In developing countries, acute rheumatic fever is the most common cause of acquired heart disease. Gelsolin is a calcium-dependent, multi-functional actin-regulatory protein circulating in the plasma of healthy human beings. The correlation between blood gelsolin levels and inflammatory conditions suggests the potential benefit of gelsolin as a prognostic marker. The aim of the present study was to appraise the association of gelsolin and acute rheumatic carditis in childhood. Materials and Methods Plasma gelsolin levels were measured and echocardiographic examinations were performed in patients (n=37) with acute rheumatic carditis and compared with those of age- and gender-matched healthy controls (n=24). Results The plasma gelsolin levels in children with acute rheumatic carditis were significantly lower compared with controls (197±218 versus 322±255 mg/L, p=0.039). There was a significant correlation among gelsolin levels and the grade of mitral regurgitation (p=0.030), left ventricular end-diastolic diameter (p=0.017), and left ventricular end-systolic diameter (p=0.028) at diagnosis. Conclusions Levels of the gelsolin plasma isoform were decreased in patients with acute rheumatic carditis compared with healthy controls. Gelsolin may be used as a biochemical marker for acute rheumatic carditis.